Juridical Analysis of Strengthening the Decision of the Administrative Court by PT TUN Jakarta in the Dispute over the Cancellation of HGB Certificate No. 1444/Kebon Kelapa (Decision Study Number 243/B/2025/PT.TUN.JKT) - Mhd. Hasbi Simanjutak; Mhd. Nasir Sitompul (International Asia Of Law and Money Laundering (IAML), 2025)
This study examines the juridical basis of The Jakarta High Administrative Court (PT TUN) in strengthening the decision of the Jakarta Administrative Court related to the dispute over the cancellation of the building rights certificate (HGB) No. 1444 / Kebon Kelapa issued by the Land Office of the city administration of Central Jakarta. The dispute is filed by the plaintiff on the pretext that the certificate is legally flawed both procedurally and substantially, so it must be declared null and void. In addition to the head of the Central Jakarta Land Office as a defendant, PT Multi Aneka Sarana also serves as defendant II intervention because it is the right holder of the HGB.The Jakarta Administrative Court in the first instance decision stated that the niet Ontvankelijk lawsuit (unacceptable) was filed after passing the 90-day grace period as determined by Article 55 of Law Number 5 of 1986 on Administrative Justice. The panel of judges considered that the plaintiff should have known the existence and validity of the certificate long before filing the lawsuit, considering that the certificate had been issued since 1989 and the land object had been controlled and utilized by the HGB holder. This decision was then re-examined at the appeal level and upheld by PT TUN Jakarta through Decision number 243/B/2025/PT.TUN.JKT.Through normative legal research methods with a statutory approach, conceptual approach, and case approach, this study found that PT TUN consistently applied the principle of termijn vervallen, which is a doctrine that states that a lawsuit filed after the passage of a mandatory grace period is otherwise unacceptable without examining the subject matter of the case. The application of this principle confirms that the provisions of the grace period in the Tun procedural law are limited and binding, so ignoring them will damage legal certainty.In addition, the study found that the reasons for the delay in filing a lawsuit put forward by the plaintiff did not meet the qualification of “justifiable juridical reasons,” based on both doctrine and judicial practice. Therefore, the consideration of PT TUN Jakarta that strengthens the PTUN decision is not only in line with positive legal norms, but also strengthens the principles of administrative order, protection for land rights holders, and stability of the National Land system.PT TUN's assertion is important to prevent misuse of certificate cancellation claims filed after a very long period of time, as well as to ensure that land administration is not constantly in a state of uncertainty. Thus, this ruling contributes to the harmonization of TUN judicial practice and provides jurisprudential guidelines for the future handling of land disputes.